Effect of Different Extracting Solvents on Antioxidant Activity and Inhibitory Effect on Diabetic Enzymes of Chlorella vulgaris and Spirulina platensis - Agustiar, Akhmad Awaludin; Rairat, Tirawat; Zeng, Mingyong; Praiboon, Jantana (Journal of Fisheries and Environment, 2022)
This study aimed to determine the effect of the solvent used in microalgae extraction on the total phenolic content (TPC), total flavonoid content (TFC), antioxidant, and anti-carbohydrate-hydrolyzing enzyme activities of the crude extracts. Algal biomass of Chlorella vulgaris and Spirulina platensis was extracted by different types of solvent, namely n-hexane, ethanol, methanol, and distilled water. Additionally, the correlations of TPC and TFC with antioxidant activity as well as anti-diabetic activity (anti-α-amylase and anti-α-glucosidase) were investigated. Results demonstrated that C. vulgaris and S. platensis methanolic extracts had the highest TPC, with values of 40.62±4.13 and 64.38±7.39 mg GAE·g-1 (mg of gallic acid equivalent per gram extract), respectively. These extracts also showed the greatest antioxidant activity, with IC50 values for DPPH (2,2-diphenyl-1-picrylhydrazyl) of 117.62±4.46 and 97.89±4.64 µg·mL-1, respectively, and ABTS (2,2-azinobis [3-ethylbenzothiazoline-6-sulfonic acid]) of 102.52±2.50 and 46.21±0.88 µg·mL-1, respectively. Furthermore, they strongly inhibited α-amylase activity (IC50 of 262.97±9.61 and 275.46±12.44 µg·mL-1) and α-glucosidase activity (IC50 of 207.09±6.97 and 169.01±3.16 µg·mL-1). TPC was positively and signiﬁcantly correlated with antioxidant and α-glucosidase inhibition activities. Meanwhile, only α-amylase inhibitory activity had a significant positive correlation with TFC. Therefore, crude methanolic extracts of C. vulgaris and S. platensis might be potential sources of natural antioxidants and anti-diabetic dietary supplements.